A study of Deep Neck Space Infections at Kathmandu University Dhulikhel Hospital - Pokharel, M.; Dhakal, A.; Rajbhandari, P.; Madhup, S. K.; Khadka, L. (Kathmandu University Medical Journal, 2021)
Background Deep neck infections are severe infections in potential spaces and fascial planes of the neck. Despite antibiotic therapy, these infections continue to cause significant morbidity and mortality. Objective To determine the clinical features, predisposing factors, socio demographic factors and complications associated with deep neck infections. Method Prospective study conducted in the Department of Otorhinolaryngology, Kathmandu University Dhulikhel Hospital between March 2018 and June 2020. Seventy-five patients with deep neck infections were enrolled. Result Submandibular abscess was most frequently observed (41.3%), followed by submental abscess (25.3%), parotid abscess(9.3%), ludwig’s angina (6.7%), posterior triangle of neck abscess (4%), retropharyngeal abscess (2.7%), parapharyngeal space abscess (2.7%), and multiple space infections (8%). Staphylococcus aureus was the most common organism (53.3%), followed by Beta hemolytic Streptococcus (12%) and methicillin-resistant Staphylococcus aureus (12%). A negative culture was seen in 22.7%. Sixty-eight percent of patients underwent incision and drainage. Incision and drainage with dental extraction was done in 26.7%, four percent underwent incision and drainage with debridement and dental extraction, whereas 1.3% underwent incision and drainage with tracheostomy. Eight percent patients required Intensive care unit admission. Seven patients had descending mediastinitis, four out of which developed sepsis. When age and duration of hospital stay were correlated by using Pearson correlation coefficient, a remarkable correlation was observed (p=.020). Noteworthy relationship was not observed between different locations of deep neck infections and duration of hospital stay (p=.202). Conclusion Early identification of deep neck infections is often challenging. Proper knowledge and extreme vigilance is necessary when dealing with these complex entities to avoid life-threatening complications.